Decision-making in wildlife forensics: comparing complex and simple cases at the Wyoming Game and Fish Laboratory - Frazier, Kimberly M.; Bauman, Tasha L. (Frontiers in Ecology and Evolution, 2025)
This study compares the decision-making processes and workflows of complex and simple wildlife forensic cases at the Wyoming Game and Fish Wildlife Forensic Laboratory. To highlight the varied processes involved in analyzing cases at the laboratory, a complex case, consisting of eighteen different animals and a simpler case consisting of only two animals will be discussed. Both cases highlight several decision making points throughout to determine the number of samples to collect, if the samples contain biological material, the extraction methods to be used, and how to proceed with downstream analyses. These decision points are notably more numerous in the complex case. Both cases cover the process of subsampling, extraction methods, test methods, and results. At the time of the complex case, sanger sequencing, used for species identification of the deer species did not allow for the differentiation between the closely related white-tailed deer (Odocoileus virginianus) and mule deer (Odocoileus hemionus) and a protein analysis was used to differentiate them. A new procedure, population assignment in conjunction with sequencing, validated after the complex case and prior to the simple case made the differentiation easier and more efficient. This change in species identification emphasizes the need for continual validation of new procedures. Results of wildlife forensic cases are not only dependent on the analyses performed, but also on the decisions made by the analyst throughout the process.